Clinical Significance of Rasayana Therapy in Management of Cancer (AYUSHDHARA, 2024)
Cancer has faced medical experts with challenges due to its dreadfulness and the harmful consequences of existing therapies. It is the second most common non-communicable illness after ischemic heart disease. Extensive research has resulted in several innovative healing modalities and hundreds of cancer treatments. Surgical excision is the most established and well-tested therapy option. Radiation treatment is successful in managing a wide range of malignant tumours and is used to treat around half of all cancer patients. Cancer is the most prevalent cause of mortality globally. It has resulted in around 10 million fatalities by 2020, accounting for nearly one in every six deaths. Breast, lung, colon, and rectum prostate cancers are the most prevalent. Various studies have demonstrated that, despite advancements in cancer therapies, there remain various unmet requirements of cancer patients that vary depending on the stage and kind of disease. Unmet requirements in cancer patients have been linked to increased symptom discomfort, anxiety and a lower quality of life. Several research studies have revealed that cancer patients seek out complementary and alternative medicines (CAM) to address these unmet needs. In India, Ayurveda is the most often utilised alternative therapy that patients employ. Our previous research papers. Several case studies have demonstrated that the Rashadis-based Rasayana therapy procedure has a high potential for enhancing therapeutic outcomes in cancer patients. In this article, we discussed the therapeutic use of Rasayana treatment cancer. Rasayana helps in the replenishment and enhancement of Dhatus and Ojas. Rasayana therapy's primary advantages are Deerghayu, Smriti, Medha, Arogyam, Tarunam Vaya, Prabha, Varna, Swararodarya, Indriya Balam, Vaksidhi, Pranati, and Kanti.